Influence of nanostructured ITO films on surface recombination processes in silicon solar cells - Kostylyov, V.P.; Sachenko, A.V.; Serba, O.A.; Slusar, T.V.; Vlasyuk, V.M.; Tytarenko, P.O.; Chernenko, V.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2015)
This paper describes the results of comparative studies of illumination currentvoltage characteristics and spectral characteristics of silicon solar cells with rear location of the collector p-n-junction for the cases of non-passivated and passivated front illuminated surface. Passivation was performed by silicon dioxide layer or ITO layer. It was found that ITO layer surface passivation with formation of ITO/silicon heterojunction, unlike silicon dioxide layer passivation, leads to a significant reduction of the effective surface recombination velocity. It significantly increases the value of the internal quantum efficiency in the wavelength range from 550 to 1050 nm and, as a result, significantly increases the value of short-circuit current of solar cells.